2011
DOI: 10.1136/jamia.2010.006486
|View full text |Cite
|
Sign up to set email alerts
|

The patient and the computer in the primary care consultation

Abstract: This study demonstrates that in consultations where doctors use computers, the computer can legitimately be regarded as part of a triadic relationship. Routine use of computers in the consultation changes the doctor-patient relationship, and is altering the distribution of power and authority between doctor and patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 27 publications
0
66
0
Order By: Relevance
“…38 That being said, patients have different styles and may have differing levels of comfort with the computer; the physician must assess this and modulate the amount of screen sharing if needed. 55 …”
Section: Setting the Stage 1 Room Set Upmentioning
confidence: 99%
“…38 That being said, patients have different styles and may have differing levels of comfort with the computer; the physician must assess this and modulate the amount of screen sharing if needed. 55 …”
Section: Setting the Stage 1 Room Set Upmentioning
confidence: 99%
“…29,30,50 Eight studies described variation in the amount and manner in which the EMR was used. 15,36,39,41,46,48,51,54 Four studies examined typing behaviors 33,37,42,48 and six reported on screen positioning, with only 8-10 % active screen sharing during the visit. 29,30,33,37,38,52 Interestingly, one study noted patients had a more positive attitude towards the EMR when they were shown the screen.…”
Section: Characterizing Emr Communication Behaviorsmentioning
confidence: 99%
“…Researchers are investigating how specific EHR features or single communication modalities (i.e. speech) correlate with EHR use, as well as how the introduction of new computing devices start to play the role of a third entity in the medical office environment, thereby enabling a novel triadic interaction between physician, patient and EHR [43]. For instance, Darmon and colleagues [11] studied 15 EHRs in France to assess functionalities across systems.…”
Section: Related Workmentioning
confidence: 98%